THE INHIBITING FACTORS OF FERTILITY RATE DECREASE AND THE DIRECTION OF FAMILY PLANNING PROGRAM REVITALIZATION - Darwin, Muhadjir; Susilastuti, Dewi Haryani; Tsalatsa, Yam’ah; Setianingrum, Triyastuti; Sumini, Sumini (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2015)
This paper analyzes stagnation of fertility rate decrease in Indonesia. Population balance can be achieved by controlling fertility. Indonesian survey of demography and health in 2012, however, shows no significant difference of fertility rates from similar surveys in 2002 and 2007. In addition to that, there are factors such as the shifting political paradigm in the developing world, change of local governance, and institutional change that influence the stagnation of fertility rate decrease. This writing recommends ways to accommodate balance between democratic system and effective achievement. Besides, the decrease of fertility rate also requires serious commitment and determination of local government to participate. For this goal, sociological and cultural model can be used as an alternative to transform the behavior of society.